MICROPLASTICS: TINY STUFF, BIG THREAT TO FRESHWATER ECOSYSTEMS - Rossember; Belén; Karol Lúcia; Kristha; Andrea; Marcela Inés (Ciência Animal, 2024)
Microplastics are tiny plastic particles that we humans produce, and they are constantly moving around our planet. They have become a very serious concern to the environment, because we produce them in huge quantities, and they are very slow to degrade. When microplastics reach freshwater environments, they can pollute drinking water, affect all kinds of life forms, and find their way to our diet. Many international organizations are trying to reduce the use and production of articles like bags, clothes, hygiene products and even toys, that are made of or contain microplastics. Researchers all over the world are looking into ways to degrade microplastics, and to discover new, eco-friendly materials. But there are many things we all can do to help as well. All of us can make a difference to reduce microplastics pollution.